Jalinan: enhancement project of Resource Centre in KAED, IIUM through the concept of interconnectedness - Saleem, Nur Jannah Najihah; Muhamad Salehuddin, Amirah Adlina; Ayob, Mohd Fairullazi; Hamat, Sufian; Awang, Arita Hanim; Mohd Din, Azrin; Abdullah, Fadzidah; Raja Abdul Rahman, Raja Intan Suhaylah (IIUM Press, 2024)
Resource Centre of the Kulliyyah of Architecture and Environmental Design (KAED) is significant in assisting academic activities and research. However, the KAED Resource Centre confronts challenges due to neglect, which limits its impact on learning and research productivity. The project intends to enhance the Resource Centre's visibility and accessibility, therefore encouraging increased participation among educators as well as students. The goals are to raise awareness of its services, to enhance physical and digital access to resources, and to provide a friendly environment that promotes cooperation and learning. The method consists of a thorough site analysis to evaluate present facilities and user experience, a literature research to find best practices in resource centres design, and precedent studies of similar facilities to develop effective engagement methods. The findings are design solutions, with an emphasis on physical space improvements, improved resource organisation, and the use of technology to enhance user experience. Ultimately, this initiative seeks to make the KAED Resource Centre a more effective and engaging focus for academic and research excellence among the KAED community.